Colorimetric detection of influenza A virus using antibody-functionalized gold nanoparticles1. Issue 12 (21st June 2015) - Liu, Yuanjian; Zhang, Linqun; Wei, Wei; Zhao, Hongyu; Zhou, Zhenxian; Zhang, Yuanjian; Liu, Songqin
<x xml:space="preserve">Abstract</x> A colorimetric immunosensor for IAV based on AuNPs modified with mAb is developed. This assay depends on an ordered AuNPs structure covering the virus surface and can be applied to any viral pathogen by incorporating the appropriate pathogen-specific antibody, giving the proposed method a broad prospect in clinical diagnosis applications.